2016
DOI: 10.1063/1.4963112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local fields on the Mg acceptor in GaN films and GaN substrates

Abstract: The electron paramagnetic resonance (EPR) spectrum of the Mg acceptor is studied in a variety of GaN samples, including mm-thick free-standing substrates and sub-micron heteroepitaxial films. The former allows a view of the acceptor unique for EPR—in an environment with less than 107 cm−3 dislocations and doping densities ranging from 4 × 1016 to 6 × 1018 cm−3. By probing Mg in a broad range of samples in one study a new feature of the acceptor emerges. The EPR data reveal an anisotropic line shape that reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Thinfilm MOVPE g-factors were determined to be g || = 2.08 and g ⊥ = 1.99 and those of the MME sample, g || = 2.06 and g ⊥ = 2.01. The g-factor anisotropy is consistent with earlier work [12,19,28]. As discussed by others, the g-factor anisotropy seen in the thin-film samples (g || − g ⊥ = 0.09 and g || − g ⊥ = 0.05) compared to the free-standing crystals (g || − g ⊥ ≈ 1.9) reflects a decrease in the local non-axial crystal field Δ x [13,14].…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Thinfilm MOVPE g-factors were determined to be g || = 2.08 and g ⊥ = 1.99 and those of the MME sample, g || = 2.06 and g ⊥ = 2.01. The g-factor anisotropy is consistent with earlier work [12,19,28]. As discussed by others, the g-factor anisotropy seen in the thin-film samples (g || − g ⊥ = 0.09 and g || − g ⊥ = 0.05) compared to the free-standing crystals (g || − g ⊥ ≈ 1.9) reflects a decrease in the local non-axial crystal field Δ x [13,14].…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, the line width varies linearly with frequency as the angle between the c axis and applied magnetic field increases, indicating increasing contributions from ∆g ⊥ . The frequency dependence of the linewidth shown in figure 4(b) as well as the variation exhibited at different angles verifies the assumption of g-strain suggested by Zvanut et al, and provides further verification of the crystal field model suggested by Aliev et al [12,19].…”
Section: Frequency Dependencesupporting
confidence: 83%
See 2 more Smart Citations
“…At this juncture, we also point out that the results obtained thus far can also be helpful to gauge the accuracy of various theoretical approximations and numerical methods used to study the properties of systems with circular symmetry. This situation may apply to certain 2D compositions formed in semiconductor quantum dots, heterostructures or thin films [ 54 , 55 , 56 , 57 ] which lead to the creation of a two-dimensional electron gas (2DEG) system. In particular, the physics of quantum Hall effect (QHE) has at its heart the model of a 2D system of electrons confined in a neutralizing background represented by a uniformly charged circular disk lying on the same plane as the layer of electrons [ 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%